Environmental drivers of ant dominance in a tropical rainforest canopy at different spatial scales. (29th November 2020) - Antoniazzi, Reuber; Guevara, Roger; García‐Franco, José; Janda, Milan; Leponce, Maurice; Dáttilo, Wesley
Abstract : Tropical trees accommodate a high co‐occurrence of ant species, mainly due to the high diversity of microhabitats available. However, a few ant species are highly abundant, dominating resources and defending territories in tree canopies. Although arboreal ants have been studied extensively, little is known about the structural drivers of ant spatial dominance in tropical rainforest canopies. This study investigated whether canopy tree microhabitats and micro‐environmental factors (given by branch characteristics and spatial position of sampling points within tree crowns) are determinants of ant presence and species composition in a Mexican tropical rainforest. It also analysed whether whole tree characteristics, that is, the tree canopy, given by tree size and epiphyte/climbing plant richness and abundance, could determine ant spatial dominance of food resources. This study found a higher probability of ant presence on baits lower in the canopy, probably a result of ants foraging in the zones between the treetops and the ground layer. No microhabitat or micro‐environmental variables were related to ant species composition. It also observed less dissimilarity of species composition between baits and between trees than between plots, revealing that each plot presents a unique set of species. Moreover, increased tree height and epiphyte/climbing plant abundance (i.e., structural heterogeneity and greater foraging area) and lower epiphyte/climbing plant richness led to decreasing ant dominance. This study's findings reveal that, while micro‐environmental factors have almost no influence on the foraging of dominant ant species within canopy trees, the size and heterogeneity of trees shape ants' spatial dominance. Abstract : The probability of an ant occurring on a canopy bait is higher when this bait is located lower in the canopy. Increased tree height and a higher abundance of epiphyte/climbing plants contributed to the lower dominance of ant species at the tree crown scale. Ant foraging patterns in tropical tree crowns were scale‐dependent, shaped by distinct spatial scales within and among trees and plots.